Endodontic management of permanent mandibular canine with Type II canal configuration using cone-beam computed tomography. A Case report - Hadi Rajeh Alfahadi; Ahmed Mohammed Alghamdi (Wolters Kluwer Medknow Publications, 2020)
Mandibular canines, in most cases, have one root and one canal. Some investigators reported a morphological variation in mandibular canals. This report documented a case of mandibular canine of a healthy 53-year-old female patient referred for evaluation of deep caries located in the buccocervical region of the crown, which had reached the pulp chamber. Cone beam computed tomography revealed one root with two canals (Vertucci Type II). A diagnosis of symptomatic irreversible pulpitis and asymptomatic apical periodontitis was established, and nonsurgical root canal treatment was performed with the help of dental operating microscope. The use of good diagnostic tools improves the accuracy of the diagnosis and the success of the treatment.